FRI0150 Maintenance of remission in rheumatoid arthritis patients with low-moderate disease activity following withdrawal of certolizumab PEGOL treatment: Week 52 results from the certain study. (23rd January 2014) - Smolen, J.S.; Emery, P.; Ferraccioli, G.; Samborski, W.; Berenbaum, F.; Davies, O.; Koetse, W.; Bennett, B.; Burkhardt, H.
Abstract : Background: Certolizumab pegol (CZP) increased rates of remission and low disease activity (LDA) as an addition to non-biologic DMARDs in rheumatoid arthritis (RA) patients (pts) with long-standing, low/moderate disease activity (DA). 1 Objectives: To evaluate the maintenance of remission to week (Wk) 52 in pts with low/moderate DA following treatment (tx) withdrawal after 24Wks of CZP or placebo (PBO). Methods: CERTAIN, a double-blind (DB), randomized, Phase IIIb study, enrolled pts with low to moderate DA (CDAI >6 and ≤16) (NCT00674362 ). Following 24Wks DB phase (CZP 400mg/PBO at Wks 0, 2, 4, then CZP 200mg/PBO every 2 Wks [Q2W]) pts in CDAI remission (≤2.8) at both Wks 20 and 24 stopped randomized tx but remained on conventional DMARDs; remitters who flared between Wk24 and Wk52 were retreated with CZP. Pts not in remission who withdrew at Wk24 entered an open-label extension. Primary endpoint was CDAI remission at both Wks 20 and 24 (NRI). Secondary endpoints included maintenance of CDAI remission when randomized tx was stopped. Results: Baseline (BL) characteristics (means) were similar for CZP (n=96) vs. PBO (n=98) pts. A greater proportion of CZP pts than PBO pts were in LDA or remission at Wk12 and Wk24 (Fig.A ). Over 3 times as many CZP pts had CDAI remission at both Wks 20 and 24 vs. PBO (18.8% vs. 6.1%, p<0.05). 1 Lower HAQ and pain scores at BL were associated with improved CDAI DA status at Wk24 for CZP and PBO. At Wk24, 18 prior CZP (1 pt withdrew before the first efficacy measurement) and 6 prior PBO pts stopped therapy. CDAI remission was retained up to Wk52 in 3/17 prior CZP vs. 2/6 prior PBO pts, with 7/17 vs. 2/6 pts in CDAI remission/LDA at Wk52. SDAI remission was observed in 4/17 prior CZP vs. 2/6 prior PBO pts, and DAS28(ESR) remission in 4/17 pts vs. 1/6 pt. Median time to loss of CDAI remission (all pts) was 42.5 days (Fig.B). Conclusions: In RA pts with long-standing low/moderate DA, addition of CZP to non-biologic DMARDs increased rates of remission and LDA and inhibited progression to high DA. On stopping CZP therapy, most pts were unable to maintain remission, which may have implications for stopping TNF inhibitor therapy in this pt population. References: Smolen et al. Ann Rheum Dis 2011;70(Suppl3):25 Disclosure of Interest: J. Smolen Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, P. Emery Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, G. Ferraccioli: None Declared, W. Samborski Consultant for: UCB Pharma, F. Berenbaum Consultant for: UCB Pharma, O. Davies Employee of: UCB Pharma, W. Koetse Employee of: UCB Pharma, B. Bennett Shareholder of: UCB Pharma, H. Burkhardt Consultant for: UCB Pharma